Problemy pomiaru niemetrycznych zmiennych objaśniających w modelowaniu ekonometrycznym wartości rynkowej nieruchomości - Pawlukowicz, Roman (The Issue of Non-Metric Explanatory Variables in Econometric Modelling of Property Market Value, 2007)
In Polish practice econometric models are especially significant, are permitted for property valuation. The studies of the property market prove non-metric variables to be fundamental factors in the changeability of transaction prices of properties and hence their market value. In property valuation they figure as ordinal variables (metric variables are formulated similarly). The article presents a short outline of methods for measuring non-metric explanatory variables of econometric model and simultaneously, a suggestion is made to solve the problem through the usage of the conjoint analysis to determine the execution of these methods, which will later be used to estimate the econometric model. The solution is applly in a particular instance of econometric modelling of a property's market value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 436-444